The Effectiveness on the Realization of the Government Internal Supervisory Apparatus Function to the Implementation of Regional Government - Alvin Daniel Silaban; Yolanda Wynne Maria Pasaribu; Farra Shalma (Universitas Kuningan, 2020)
This paper aims to analyze the importance of supervisory function in ensuring the government effectiveness and efficiency in the realization of good governance principles. The government internal supervisory apparatus is an authorized institution or agency. In the application of supervisory function in regional government, they must be able to carry out its duty properly based on the prevailing laws and regulations. This study employed juridical-empirical method. The results showed the duties and the function are stipulated on the Government Regulation Number 60 of 2008, the government internal control system which includes the audits, reviews, evaluation, monitoring, and other supervisory activities. In addition, it is also stated in the Regulation of the Ministry of Home Affairs Number 64 of 2007, the technical guidelines and the working procedures of the provincial and regency/city inspectorate. The conclusion is the role of the government internal supervisory apparatus often faces some problems in doing their duties and functions. For instances, rampant corruption cases committed by regional officials making the effectiveness of the role of the government internal supervisory apparatus being questioned. Furthermore, their low capability and the independence issues encountered by regional government hampers the performance of the Government Internal Supervisory Apparatus which is directly responsible to regional head. This practice also seems to be able to reduce the objectivity and the independence of the regional government of internal supervisory apparatus in doing their supervisory dutiesTujuan dari penulisan ini yaitu untuk menganalisis fungsi pengawasan menjadi sangat penting dalam menjamin penyelenggaraan pemerintah yang efektif dan efisien untuk mewujudkan asas tata pemerintah yang baik (good governance). Aparat Pengawas Intern Pemerintah sebagai institusi atau lembaga yang berwenang dalam menjalankan fungsi pengawasan di pemerintahan daerah harus mampu melaksanakan fungsi pengawasan tersebut dengan baik sesuai dengan peraturan perundang-undangan yang berlaku . Metode penelitian yang digunakan yaitu yuridis empiris. Hasil penelitian menunjukan bahwa tugas dan fungsi diatir oleh Peraturan Pemerintah Nomor 60 Tahun 2008 tentang Sistem Pengendalian Intern Pemerintah, melalui audit, reviu, evaluasi, pemantauan, dan kegiatan pengawasan lainnya dan Peraturan Menteri Dalam Negeri Nomor 64 Tahun 2007 tentang Pedoman Teknis Organisasi dan Tata Kerja Inspektorat Provinsi dan Kabupaten/Kota. Simpulan bahwa Peran Aparat Pengawas Intern Pemerintah kerap kali menghadapi kendala-kendala dalam melaksanakan tugas dan fungsinya. Salah satunya adalah mengenai kasus korupsi yang marak dilakukan oleh pejabat daerah, menyebabkan dipertanyakannya efektivitas peran pengawasan Aparat Pengawas Intern Pemerintah Daerah. Selain itu, kapabilitas Aparat Pengawas Intern Pemerintah yang rendah dan masalah independensi yang dihadapi oleh Aparat Pengawas Intern Pemerintah Daerah menghambat kinerja Aparat Pengawas Intern Pemerintah yang secara langsung bertanggung jawab kepada kepala daerah. Praktik tersebut juga dianggap memungkinkan mengurangi objektivitas dan independensi Aparat Pengawas Intern Pemerintah Daerah dalam menjalankan tugas pengawasannya